Pendampingan dalam Program Bantuan Stimulan Perumahan Swadaya (BSPS) NAHP di Kelurahan Potoro - Algiffari, M. Fauzhan; Ajami, Frans Mitran; Pido, Rifaldo (Insan Kreasi Media, 2023)
Self-supporting housing construction carried out by the community in general still does not meet liveable quality, tends to sprawl (irregularly) and is well-organized based on a lack of infrastructure and facilities that meet the requirements of a healthy environment. Things like this tend to make settlements wider and form separate slum neighbourhoods. In order to improve the quality of people's housing, it is important to make efforts to make people aware that building healthy housing is the responsibility of the people themselves. Therefore, empowerment is an effort that must be carried out by strengthening the power possessed by each community. In addition, positive steps and directions are needed to create a conducive environment and atmosphere for every actor involved in housing development, especially for residents. Strengthening the provision of facilities and support in opening access and opportunities that can make the community more empowered. For this reason, the Government is carrying out the Self-Help Housing Stimulant Assistance (BSPS) Assistance Activities.